Plan de marketing para mejorar el posicionamiento de la industria “Molinos San Luis” ubicada en la provincia de Cotopaxi cantón Saquisilí en el período 2015-2016 - Freire Martínez, Juan Gabriel (2016)
The present research had like objective design a Marketing Plan to improve the positioning of the industry “San Luis Mill” located in the Cotopaxi Province – Saquisilí Canton in the period 2015-2016”, which was developed with the purpose of help to increase the sales level and the income that possess actually, for that reason this industry has the necessity to look for solutions to improve the situation in the future and guarantee the stay in the market, in other words the Marketing Plan is established like a possible solution that permits do an analysis of the actual situation of the industry in order to detect the lack and set up corrections taking advantage of the strengths and opportunities of the industrial’s environment.